CYBERSECURITY IN THE ERA OF REMOTE WORK (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The rise of remote work, accelerated by the COVID-19 pandemic, has reshaped the modern workforce and introduced new challenges in cybersecurity. As employees increasingly rely on home networks, personal devices, and cloud-based services, organizations face heightened risks of data breaches, phishing attacks, and unauthorized access. This paper explores the primary cybersecurity threats associated with remote work, analyzes strategies companies can adopt to safeguard digital assets, and provides best practices for employees to minimize risks. Emphasis is also placed on the evolving landscape of cybersecurity, including the adoption of Zero Trust frameworks and AI-driven security systems. Ensuring cybersecurity in a remote work environment requires a shared responsibility between organizations and individuals, along with continuous adaptation to emerging threats.